Associative CAD references in the neutral parametric canonical form. Issue 4 (7th June 2017) - Staves, Daniel R.; Salmon, John L.; Red, Walter E.
ABSTRACT: Due to the multiplicity of computer-aided engineering applications used in industry, interoperability between programs has become increasingly important. A 1999 study by the National Institute for Standards and Technology (NIST) estimated that inadequate interoperability between the original engineering manufacturers (OEM) and their suppliers cost the US automotive industry over $1 billion per year, with the majority spent fixing data after translations. The Neutral Parametric Canonical Form (NPCF) prototype standard developed by the BYU Site of the NSF Center for e-Design offers a solution to this problem by enabling real-time collaboration between heterogeneous systems while preserving design intent. The NPCF is implemented within a SQL database and defines the schema both for neutral features and for the parameters defining the inter-feature relationships and associations. GRAPHICAL ABSTRACT: